FORMAÇÃO DO SUJEITO AUTÔNOMO NA SOCIEDADE - Guimarães, Solange (Revista Formadores, 2004)
Trabalho elaborado considerando o princípio da autonomia como parte integrante e fundamental da educação em valores e sua importância nos processos educativos para a formação do sujeito, que preparem para a relação deste com o desenvolvimento da sociedade da qual participa e recebe influências. Reflete sobre a dialética autonomia/heteronomia no processo educativo, na consideração dos referenciais teóricos de abordagens existentes sobre essa temática, enquanto remete aos principais resultados de uma investigação realizada nas Faculdades Adventistas de Educação do Brasil, Cursos de PedagogialFAEB-CP, no contexto de uma proposta pedagógica e suas bases axiológicas. ABSTRACT The purpose of this artic1e is to bring the principle of autonomy into focus, showing it as an essential part of education in values. It also points to the importance of autonomy in the educational processes leading to the integral formation of the individual and to the training that he or she must receive in order to relate to the development of the society to which he or she belongs. This is a reflection upon the dialectics that exists between autonomy and heteronomy within the educational practice by focusing on the theoretical framework of previous approaches to this subject while taking into consideration the most important end results of a research effort undertaken at the Seventh-Day Adventist Schools of Education in Brazil within the context of their pedagogic plan and axiological foundations.